2015
DOI: 10.1016/j.bbmt.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Characteristics and Outcomes of Trial Participants and Nonparticipants: Example of Blood and Marrow Transplant Clinical Trials Network 0201 Trial

Abstract: BACKGROUND Controversy surrounds the question of whether clinical trial participants have better outcomes than comparable patients who are not treated on a trial. We explored this question using a recent large, randomized, multi-center study comparing peripheral blood (PB) with bone marrow (BM) transplantation from unrelated donors (URD), conducted by the Blood and Marrow Transplant Clinical Trials Network (BMT CTN). METHODS AND FINDINGS We compared characteristics and outcomes of study participants (n=494) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 24 publications
(26 reference statements)
0
20
0
Order By: Relevance
“…This is contrary to what has been reported in other studies. 3336 It is also interesting to note that no deaths in the bone marrow graft group were due to graft failure. It is unclear why those patients with BM had poorer survival; however our study is limited in that only a small number of subjects received bone marrow grafts (16%).…”
Section: Discussionmentioning
confidence: 98%
“…This is contrary to what has been reported in other studies. 3336 It is also interesting to note that no deaths in the bone marrow graft group were due to graft failure. It is unclear why those patients with BM had poorer survival; however our study is limited in that only a small number of subjects received bone marrow grafts (16%).…”
Section: Discussionmentioning
confidence: 98%
“…Unfortunately, most such data currently come from trials testing unapproved treatments. Although few studies compare outcomes of patients enrolled in CER studies to those of patients not enrolled, findings from one highly visible CER study (SUPPORT 2010) and other retrospective analyses (Foglia et al 2015) seem to suggest that participating in a CER randomized study may be associated with better, if not equivalent, outcomes (Khera et al 2015;Lantos and Feudtner 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Identification and review of research literature We identified nine eligible studies that included twelve comparisons of trial and non-trial patients: Arrieta et al [28], Bertelli et al [29], De Placido et al [30], Field et al [31], Goldman et al [32], Khera et al [33], Led Du et al [34], Svensson et al [35] and Templeton et al [36]. Figure 2 contains a PRISMA flow diagram showing the selection of studies.…”
Section: Strategies For Dealing With Dilemmasmentioning
confidence: 99%
“…Characteristics of the studies All nine studies included comparisons concerning overall survival [28][29][30][31][32][33][34][35][36], some also included progression-free survival [29,30,32,34]. Eight of the nine studies were retrospective cohort The Kaplan-Meier analyse showed a trial effect (p = 0.007), but the univariate Cox proportional hazard ratio did not (p = 0.089) studies.…”
Section: Strategies For Dealing With Dilemmasmentioning
confidence: 99%
See 1 more Smart Citation